Redistribuição de sedimentos em encostas por meio do C total e do isótopo 13C - Queiroz, Rosemar de (2017)
High intensity of rains, associated with inadequate management in agricultural areas, have been caused loss of large volumes of soil by erosion, leading the sediments and nutrients to the hydric sources. The loss of sediments in hydrographic basins is a complex problem that requires studies to enable an understanding this dynamic, however, methods to describe and determine the dynamics of sediments without erosive process in river basins are still expensive and time consuming. One way used to evaluate and describe a dynamic of sediments is by isotope 137Cs, however, this method has a high cost to carry out analyzes, therefore, it is sought alternatives to know how sediment distribution on the slopes and/or hydrographic basins, using procedures that have lowest cost of analyses. One possibility is use the total C and 13C, because they have an uniform distribution in a soil profile and they are strongly associated with the soil mineral particles, being transferred and accumulated depending on how the sediment movement in the basin occurs. The present study evaluated a distribution of the C and 13C in two agricultural slopes with different cropping systems No-tillage (PD) and conventional tillage (PC) and the potential of total C and 13C to be used as alternatives for soil erosion inventory studies. For this, the results obtained by total C and 13C were compared with the results of the 137Cs, seeking to perceive the potential use of C and 13C as a supplier of qualitative information about sediment redistribution in agricultural slopes. In the profiles, layers were evaluated every 3 cm to a depth of 96 cm (or less if the profile it is less than that). The analysis of isotopic abundance of total C and 13C was done by mass spectrometry. The 137Cs were determined by spectrometry, without GeHP - Gamma spectrometry detectors using Germanic crystal. The data of total C and 13C do not show sediment redistribution in the PD, but, into the PC system is possible to perceive that there was intense movement of soil and C along slope. The 13C is efficient to demonstrate in what soil profiles happened the sediment redistribution along the slope, in areas that the vegetation has been replaced. Keywords: Conventional tillage; No-tillage; 137Cs; Soil Erosion; Carbon Loss.